2022
DOI: 10.1186/s12868-022-00769-x
|View full text |Cite
|
Sign up to set email alerts
|

Laser speckle contrast imaging for blood flow monitoring in predicting outcomes after cerebral ischemia-reperfusion injury in mice

Abstract: Background In the treatment of ischemic cerebral stroke (ICS), most conventional treatments, including carotid endarterectomy and carotid artery stenting, may cause cerebral ischemia-reperfusion injury (CIRI). For treated ICS patients, changes in cerebral blood flow are directly related to brain function. At present, computed tomography perfusion, dynamic susceptibility contrast-enhanced perfusion weighted imaging and magnetic resonance arterial spin labeling perfusion imaging are used to monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“… 43 Moreover, 24 h after cerebral I/R in rats, CBF in the cerebral cortex was found to be negatively correlated with the severity of brain tissue damage in a prior study. 44 This was consistent with the outcomes of our research. Meanwhile, AST IV, Lig, and AST IV combined with Lig were demonstrated to increase CBF and reduce brain infarct volume and tissue damage.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“… 43 Moreover, 24 h after cerebral I/R in rats, CBF in the cerebral cortex was found to be negatively correlated with the severity of brain tissue damage in a prior study. 44 This was consistent with the outcomes of our research. Meanwhile, AST IV, Lig, and AST IV combined with Lig were demonstrated to increase CBF and reduce brain infarct volume and tissue damage.…”
Section: Discussionsupporting
confidence: 92%
“…43 Moreover, 24 h after cerebral I/R in rats, CBF in the cerebral cortex was found to be negatively correlated with the severity of brain tissue damage in a prior study. 44 This was consistent with the outcomes of our re- in impaired mitochondrial membrane potential and ultimately aggravating tissue injury. 47 Prior studies found that AST IV 48,49 and Lig 30,31 could alleviate I/R-induced apoptosis by maintaining the mitochon- pathophysiological injury of damaged mitochondria on neurons.…”
Section: Ast IV Combined With Lig Regulated Drp1 Sumoylation Correcti...supporting
confidence: 89%
See 1 more Smart Citation
“…Preclinical studies showed that Laser speckle contrast imaging can be used to measure cerebral blood flow in mice [78]. Laser Speckle Contrast Imaging is a non-invasive optical method with high temporal and spatial resolution that relies on the phenomenon known as "laser speckle," which occurs when a laser beam illuminates a surface (such as tissue) and creates a random interference pattern.…”
Section: New Technologiesmentioning
confidence: 99%
“…[172,173] With the further development of approach, the CBF changes caused by cerebral ischemia re-perfusion injury were monitored. [174] Besides, different approaches for assessment of CBF changes during activation in the somatosensory cortex by repetitive whisker stimulation have been analyzed. [175] It has been shown that principal component analysis (PCA) can significantly reduce the noise in speckle contrast data.…”
Section: Brain Vasculature Assessmentmentioning
confidence: 99%